Angelfall - Ee, Susan (Ee, Susan. Penryn & the end of days, 2012)
It's been six weeks since angels of the apocalypse descended to demolish the modern world. Street gangs rule the day while fear and superstition rule the night. When warrior angels fly away with a helpless little girl, her seventeen-year-old sister Penryn will do anything to get her back. Anything, including making a deal with an enemy angel. Raffe is a warrior who lies broken and wingless on the street. After eons of fighting his own battles, he finds himself being rescued from a desperate situation by a half-starved teenage girl. Traveling through a dark and twisted Northern California, they have only each other to rely on for survival. Together, they journey toward the angels' stronghold in San Francisco where she'll risk everything to rescue her sister and he'll put himself at the mercy of his greatest enemies for the chance to be made whole again.